Holmium laser vs. conventional (cold knife) direct visual internal urethrotomy for short-segment bulbar urethral stricture: Outcome analysis - Jhanwar, Ankur (Can Urol Assoc J, 2016)
INTRODUCTION: Our goal was to analyze the outcome between holmium laser and cold knife direct visual internal urethrotomy (DVIU) for short-segment bulbar urethral stricture. METHODS: We conducted a prospective study comprised of 112 male patients seen from June 2013 to December 2014. Inclusion criterion was short-segment bulbar urethral stricture (≤1.5cm). Exclusion criteria were prior intervention/urethroplasty, pan-anterior urethral strictures, posterior stenosis, urinary tract infection, and those who lost to followup. Patients were divided into two groups; Group A (n=58) included cold knife DVIU and group B (n=54) included holmium laser endourethrotomy patients. Patient followup included uroflowmetry at postoperative Day 3, as well as at three months and six months. RESULTS: Baseline demographics were comparable in both groups. A total of 107 patients met the inclusion criteria and five patients were excluded due to inadequate followup. Mean stricture length was 1.31 ± 0.252 cm (p=0.53) and 1.34 ± 0.251 cm in Groups A and B, respectively. Mean operating time in Group A was 16.3 ± 1.78 min and in Group B was 20.96 ± 2.23 min (p=0.0001). Five patients in Group A had bleeding after the procedure that was managed conservatively by applying perineal compression. Three patients in Group B had fluid extravasation postoperatively. Qmax (ml/s) was found to be statistically insignificant between the two groups at all followups. CONCLUSIONS: Both holmium laser and cold knife urethrotomy are safe and equally effective in treating short-segment bulbar urethral strictures in terms of outcome and complication rate. However, holmium laser requires more expertise and is a costly alternative.